What is the point of tips?. Issue 1 (12th August 2013) - Adamczyk, L; Simpkin, A; Oxley, J
Abstract : Aims: To look at the incidence of tip margin involvement in skin excisions for basal cell carcinomas (BCCs) and to examine if any factors might be used to predict margin involvement. Methods and results: All reports of BCCs by a single dermatopathologist were reviewed and 793 excisions were included from 642 patients. Whether there was BCC in the tip and whether this tip was involved were recorded together with macroscopic and microscopic factors based on the Royal College of Pathologists' (RCPath) dataset. Statistical analysis was carried out to determine associations between these factors and tip involvement. In 43 (5%) specimens the tip margin was involved and in 35 (4%) cases the peripheral lateral margin was involved. Risk factors for tip margin involvement were a lesion that was non-discernible macroscopically and most importantly, involvement of a peripheral lateral margin. Conclusions: The incidence of tip margin involvement is small and it appears unnecessary to embed the tips unless the lesion is non-discernible macroscopically or if the peripheral lateral margin is involved.